Old Bulgarian Art - What Is It? Bulgarian Art History and the Balkan Disputes over the Medieval Heritage of Macedonia (Seminar_BG, 2025)
The study is dedicated to nationalist disputes in the field of art history. It traces the historical formation of the concept of “Old Bulgarian art” against the background of Balkan polemics regarding the medieval cultural heritage of the geographical region of Macedonia. The ways in which political causes have shaped basic theses and arguments in Bulgarian and, more generally, in Balkan art history ar critically analyzed. The study also reveals the direct participation of Bulgarian and Balkan art historians and archaeologists in state policies, especially during wartime periods, when scientific expertise was mobilized to justify military occupations and to substantiate territorial claims.  References Adashinskaya, Anna. 2022. “Renaissances in Byzantium and Byzantium in the Renaissance. The International Development of Ideas and Terminology in Late Nineteenth- and Early Twentieth-Century Europe”. In: Kallestrup, Shona et al. (eds.) Periodization in the Art Historiographies of Central and Eastern Europe. New York, London: Routledge, 31–47.Aleksandrov, Lyubomir. 1948. „Prichini za upadaka na gr. Melnik“. Geografski pregled, 4–5: 43–46. [in Bulgarian]Angelov, Svetozar. 2018. „Prof. Ivan Duychev i misiyata mu v Kostur prez 1941 g.“. V: Universitetski chetenia po arhivistika, VI. Sofia: David, 109–126. [in Bulgarian]Antonova, Klemena. 2012. „Stenopisite ot Boyanskata tsarkva v balgarskata nauchna literatura (Oshte edin pogled varhu problema za Renesansa)“. Hristiyanstvo i kultura, 8 (75): 43–58. [in Bulgarian]Azmanov, Dimitar. 1995. Moyata epoha 1878–1919. Sofia: Sv. Georgi Pobedonosets. [in Bulgarian]Bakalova, Elka. 2007. „Srabskite ucheni za monumentalnata tsarkovna zhivopis ot XV vek v Bulgaria“. Zbornik radova Vizantoloshkog instituta, XLIV: 493–518. [in Bulgarian]Bakalova, Elka. 2012. “Art History in Bulgaria: Institutional Frameworks, Research Directions and Individual Scholars”. In: Rampley, Matthew et al. (eds.) Art History and Visual Studies in Europe. Transnational Discourses and National Frameworks. Leiden, Boston: Brill, 287–304.Bakalova, Elka. 2017. “Studies in Byzantine and Medieval Bulgarian Art: A Historiographical Survey”. In: Bakalova, Elka et al. (eds.) Medieval Bulgarian Art and Letters in a Byzantine Context. Sofia: American Research Center, 3–25.Bálint, Csanád. 2010. Der Schatz von Nagyszentmiklós. Archäologische Studien. Budapest: Balassi.Balș, Gheorghe. 1911. Une visite à quelques églises de Serbie. Bucharest: Charles Göbl.Baric, Daniel. 2017. « De la tranchée où l’on fouille à celle où l’on se bat ». Français et Autrichiens sur le front de la science entre Balkans et Dardanelles ». Bulletin de l’Institut Pierre Renouvin, 2 (46): 61–76.Bazaytova, Ralitsa. b.d. „Ohrid i negovite hramove“. Pravoslavie, https://www.pravoslavieto.com/poklonnichestvo/starite_bg_stolici/Ohrid/hramove.htm (posledno poseten na 11.10.2024 g.) [in Bulgarian]Born, Robert und Störtkuhl, Beate (Hg.). 2017. Apologeten der Vernichtung oder »Kunstschützer«? Kunsthistoriker der Mittelmächte im Ersten Weltkrieg. Köln: Böhlau.Boshkoviћ, Ђurђe. 1933. „N. Mavrodinov: Ednokorabnata i krastovidnata tsarkva po balgarskite zemi do kraya na XIV v.“. Prilozi za kњizhevnost, јezik, istoriјu i folklor, 13 (1–2): 216–228. [in Bulgarian]Bozhkov, Atanas. 1984. Balgarskata ikona. Sofia: Balgarski hudozhnik. [in Bulgarian]Bozhkov, Atanas. 1985. Tarnovska srednovekovna hudozhestvena shkola. Sofia: Nauka i izkustvo. [in Bulgarian]Bozhkov, Atanas. 1989. Izobrazheniyata na Kiril i Metodiy prez vekovete. Sofia: Nauka i izkustvo. [in Bulgarian]Chamardjieff, Janaki. 1904. L’architecture en Bulgarie. Sofia.Chatzhanastasíoy,  Tásos.  2016.  Antártes kai Kapetánii.  H Ethnikí Antístash katá ths boylgarikís katochís ths Anatolikís Makedonías kai ths Thrákhs 1942–1944.  Thessaloníkh:  Aví Kyriakídh. [in Greek]Chilingirov, Asen. 2013. Ohridskata „Sv. Sofia“ i neynata datirovka. Sofia: Heron Pres. [in Bulgarian]Chlepa, Eleni-Anna. 2022. The Byzantine Monuments in Modern Greece. Ideology and Practice of Restorations, 1833–1939. Athens: Kapon.Ćurčić, Slobodan. 1989. “Architecture in the Byzantine Sphere of Influence Around the Middle of the Fourteenth Century”. У: Ђурић, Војислав (уред.) Дечани и византијска уметност средином XIV века. Београд: САНУ, 55–68.Curta, Florin. 2013. “With Brotherly Love: The Czech Beginnings of Medieval Archaeology in Bulgaria and Ukraine”. In: Geary, Patrick and Klaniczay, Gábor (eds.) Manufacturing Middle Ages. Entangled History of Medievalism in Nineteenth-Century Europe. Leiden, Boston: Brill, 377–396.Daskalov, Rumen. 2013. Kak se misli Balgarskoto vazrazhdane. 10 godini po-kasno. Sofia: Prosveta. [in Bulgarian]Daskalov, Rumen. 2015. „Vrazhdata za Srednovekovieto: balgaro-rumanskite istoriografski mezhduosobitsi“. V: Daskalov, Rumen i Vezenkov, Aleksandar (sast.) Prepletenite istorii na Balkanite, t. 3. Sofia: Izdatelstvo na NBU, 286–366. [in Bulgarian]Daskalov, Rumen. 2018. Golemite razkazi za Balgarskoto srednovekovie. Sofia: Riva. [in Bulgarian]Daskalov, Rumen. 2024. Istoriografski sporove za Srednovekovieto: balgaro-srabski, balgaro-makedonski. Sofia: Universitetsko izdatelstvo „Sv. Kliment Ohridski“.[in Bulgarian]Denchev, Stoyan, i Vasileva, Sofia. 2010. Darzhavna politika za kulturno-istoricheskoto nasledstvo na Bulgaria 1878-2009. Sofia: Za bukvite. [in Bulgarian]Deroko, Aleksandar. 1962. Monumentalna i dekorativna arhitektura u sredњevekovnoј Srbiјi. Beograd: Nauchna kњiga.Dimitrov, Bozhidar. 2000. Balgarski starini v Makedonia. Sofia: Aniko. [in Bulgarian]Dímitsas,  Margaríths.  1896.  H Makedonía en líthis fthengoménis kai mnhmíis swzoménis.  Athínai:  Aví perrí. [in Greek]Dragostinova, Theodora. 2021. The Cold War from the Margins. A Small Socialist State on the Global Cultural Scene. Ithaca, London: Cornell University Press.Dzhevietska, Evelina. 2020. Yubileyno i moderno. Kirilo-Metodievskiyat razkaz prez sotsializma v Bulgaria. Sofia: Kirilo-Metodievski nauchen tsentar. [in Bulgarian]Epstein, Ann Wharton. 1980. “Middle Byzantine Churches of Kastoria: Dates and Implications”. The Art Bulletin, 2 (62): 190–207.Filov, Bogdan. 1917. “Denkmäler der thrakischen Kunst”. Mitteilungen des Kaiserlich Deutschen Archäologischen Instituts, Römische Abteilung, 32: 21–73.Filov, Bogdan. 1919. Early Bulgarian Art. Bern: Paul Haupt.Filov, Bogdan. 1924. Starobalgarskoto izkustvo. Sofia: Naroden muzey. [in Bulgarian]Filov, Bogdan. 1925. „Starorumansko i starobalgarsko izkustvo“. Zlatorog, VI (4): 191–200. [in Bulgarian]Filov, Bogdan. 1930a. „Starobalgarskata zhivopis prez XIII i XIV vek“. Balgarska istoricheska biblioteka, 3 (1): 52–96. [in Bulgarian]Filov, Bogdan. 1930b. „Starobalgarskata tsarkovna arhitektura“. Spisanie na BAN, XLIII: 1–59. [in Bulgarian]Filov, Bogdan. 1933. Geschichte der bulgarischen Kunst unter der türkischen Herrschaft und in der neueren Zeit. Berlin, Leipzig: De Gruyter.Filov, Bogdan. 1934. Miniatyurite na Londonskoto evangelie na tsar Ivan Aleksandra. Sofia. [in Bulgarian]Frfulanoviћ, Dragana. 2001. „Chiјa јe tsrkva u Doњoј Kamenitsi“. U: Zbornik radova Filozofskog fakulteta, XXVIII–XXIX. Prishtina-Blatse, 299–343.Gargova, Fani. 2017. “Medievalism, Byzantinism, and Bulgarian Politics through the Archival Lens”. In: Bildhauer, Bettina and Jones, Chris (eds.) The Middle Ages in the Modern World. Oxford: Oxford University Press, 152–167.Geary, Patrick, and Klaniczay, Gábor. 2013. “Introduction”. In: Eidem (eds.) Manufacturing Middle Ages. Entangled History of Medievalism in Nineteenth-Century Europe. Leiden, Boston: Brill, 1–9.Grabar, André. 1928. La peinture religieuse en Bulgarie. Paris: Paul Geuthner.Grabar, Andrey. 1924. Boyanskata tsarkva. Sofia: Balgarski arheologicheski institut. [in Bulgarian]Grozdanov, Tsvetan. 1980. Ohridskoto ѕidno slikarstvo od XIV vek. Ohrid: Naroden muzeј.Grozdanov, Tsvetan. 1983. Portreti na svetitelite od Makedoniјa od IX-XVIII vek. Skopјe: RZZSK.Grozdanov, Tsvetan. 2006. Kurbinovo, i drugi studii za freskozhivopisot vo Prespa. Skopјe: MANU.Grozdanov, Tsvetan. 2007. Zhivopisot na Ohridskata arhiepiskopiјa. Skopјe: MANU.Hadjimihali, Anghéliki. 1950. La sculpture sur bois. Athènes.Haydu, Ada. 2019. „V tarsene na natsionalni arhitekturni stilove v Sarbia, Rumania i Bulgaria ot sredata na XIX vek do Parvata svetovna voyna“. V: Daskalov, Rumen i dr. (sast.) Prepletenite istorii na Balkanite, t. 4. Sofia: Izdatelstvo na NBU, 420–466. [in Bulgarian]Heinich, Nathalie. 2009. La fabrique du patrimoine. « De la cathédrale à la petite cuillère ». Paris: MSH.Ignjatović, Aleksandar. 2016. U srpsko-vizantijskom kaleidoskopu, Arhitеktura, nacionalizam i imperijalna imaginacija 1878–1941. Beograd: Orion Art.Ignjatović, Aleksandar. 2019. “Legacy of the Triad: Architecture in Medieval Serbia between Style and Ideology in the Work of Aleksandar Deroko”. Serbian Architectural Journal, 11 (1): 115–140.Ivanov, Yordan. 1908. Balgarski starini iz Makedonia. Sofia: BKD. [in Bulgarian]Ivanov, Yordan. 1910. „Tsar Samuilovata stolitsa v Prespa. Istoriko-arheologicheski belezhki“. IBAD, I: 55–80. [in Bulgarian]Ivanova-Mavrodinova, Vera. 1926. „Stari tsarkvi i manastiri v balgarskite zemi (ІV-HІІ v.)“. GNM, 4 (1922–1925): 429–582. [in Bulgarian]Kanchov, Vasil. 1894. „Patuvane po dolinite na Struma, Mesta i Bregalnitsa“. SbNUNK, X: 469–535.Kanitz, Felix. 1862. Serbiens byzantinische Monumente. Wien.Kil, Mahiel. 2002. Izkustvo i obshtestvo v Bulgaria prez turskia period. Sofia: Lyubomadrie-Hronika. [in Bulgarian]Kitromilides, Paschalis. 1998. “On the Intellectual Content of Greek Nationalism: Paparrigopoulos, Byzantium and the Great Idea”. In: Ricks, David and Magdalino, Paul (eds.) Byzantium and the Modern Greek Identity. Aldershot: Ashgate, 25–33.Klaniczay, Gábor et al. (eds.). 2011. Multiple Antiquities – Multiple Modernities: Ancient Histories in Nineteenth Century European Cultures. Frankfurt, New York: Campus.Kondakov, Nikodim. 1909. Makedonia. Arheologicheskoe puteshestvie. Sankt-Peterburg: IAN. [in Russian]Koneva, Rumyana. 1998. „Krazhbata na tsennosti i sakrovishta mezhdu balkanskite darzhavi po vreme na voynite na poluostrova (1912-1918) – izraz na balkanska vzaimnost?“ V: Vodenicharov, Petar (sast.) Darove i sakrovishta: duhovna priemstvenost na Balkanite. Blagoevgrad: YuZU, 103–111. [in Bulgarian]Kott, Christina. 2006. Préserver l’art de l’ennemi ? Le patrimoine artistique en Belgique et en France occupées, 1914–1918. Brussels: Peter Lang.Kotzayeórgh-Zymárh,  Xanthípph (epim. ).  2002.  H Boylgarikí katochí sthn Anatolikí Makedonía kai th Thrákh,  1941–1944.  Thessaloníkh:  parathrhtís. [in Greek]Langer, Benjamin. 2019. »Fremde, ferne Welt«. Mazedonienimaginationen in der deutschsprachigen Literatur seit dem 19. Jahrhundert. Bielefeld: Transcript.Lori, Bernar. 2015. „Osmanskoto nasledstvo na Balkanite“. V: Daskalov, Rumen i Vezenkov, Aleksandar (sast.) Prepletenite istorii na Balkanite, t. 3. Sofia: Izdatelstvo na NBU, 367–419. [in Bulgarian]Lory, Bernard et Nathanaili, Petrit. 2002. « Le monastère de Saint-Naum (Sveti Naum/Shën Naum) ». Balkanologie, VI (1–2): 35–40.Madgearu, Alexandru. 2007. “The Dridu Culture and the Changing Position of Romania among the Communist States”. Archaeologia Bulgarica, 11 (2): 51–59.Makuljević, Nenad. 2013. “The Political Reception of the Vienna School: Josef Strzygowski and Serbian Art History”. Journal of Art Historiography, 8: 1–13.Marchetti, Christian. 2013. Balkanexpedition. Die Kriegserfahrung der österreichischen Volkskunde – eine historisch-ethnographische Erkundung. Tübingen: TVV.Marinov, Chavdar. 2019. „Balkanskata kashta“: interpretatsii i simvolni apropriatsii na narodnata arhitektura ot osmanskata epoha na Balkanite“. V: Daskalov, Rumen i dr. (sast.) Prepletenite istorii na Balkanite, t. 4. Sofia: Izdatelstvo na NBU, 467–624. [in Bulgarian]Marinov, Tchavdar. 2015. “Constructing Bulgarian Heritage: the Nationalisation of the Byzantine and Ottoman Architectures of Melnik”. In: Couroucli, Maria and Marinov, Tchavdar (eds.) Balkan Heritages: Negotiating History and Culture. Farnham: Ashgate, 77–109.Maufroy, Sandrine. 2010. « Les premiers congrès internationaux des études byzantines : entre nationalisme scientifique et construction internationale d’une discipline ». Revue germanique internationale, 12: 229–240.Mavrodinov, Nikola. 1931. Ednokorabnata i krastovidnata tsarkva v balgarskite zemi do kraya na XIV v. Sofia: NAM. [in Bulgarian]Mavrodinov, Nikola. 1935. „Vanshnata ukrasa na starobalgarskite tsarkvi“. IBAI, 8: 262–330. [in Bulgarian]Mavrodinov, Nikola. 1942. „Arheologichni i hudozhestveno-istorichni izsledvania na Makedonia“, I. Makedonski pregled, 2: 1–25.Mavrodinov, Nikola. 1943a. „Arheologichni i hudozhestveno-istorichni izsledvania na Makedonia“, II. Makedonski pregled, 4: 88–129.Mavrodinov, Nikola. 1943b. Boyanskata tsarkva i neynite stenopisi. Sofia: Balgarska kniga. [in Bulgarian]Mavrodinov, Nikola. 1946. Starobalgarskata zhivopis. Sofia: BID. [in Bulgarian]Mavrodinov, Nikola. 1959. Starobalgarskoto izkustvo. Izkustvoto na Parvoto balgarsko tsarstvo. Sofia: Nauka i izkustvo. [in Bulgarian]Mavrodinov, Nikola. 1966. Starobalgarskoto izkustvo. XI–XIII v. Sofia: Balgarski hudozhnik. [in Bulgarian]Mavrodinova, Lilyana. 1969. Tsarkvata v Dolna Kamenitsa. Sofia: Balgarski hudozhnik. [in Bulgarian]Millet, Gabriel. 1916a. L’école grecque dans l’architecture byzantine. Paris: Ernest Leroux.Millet, Gabriel. 1916b. Recherches sur l’iconographie de l’Évangile aux XIVe, XVe et XVIe siècles. Paris: Fontemoing et Cie.Millet, Gabriel. 1919. L’ancien art serbe. Les églises. Paris: De Boccard.Millet, Gabriel. 1933. « Cozia et les églises serbes de la Morava ». In Iorga, Nicolae (dir.) Mélanges offerts à M. Nicolas Iorga par ses amis de France et des pays de langue française. Paris: J. Gamber, 827–856.Milyukov, Pavel. 1899. „Hristiyanskia drevnosti Zapadnoy Makedonii“. IRAIK, IV: 21–151.Minea, Cosmin. 2022. “From Byzantine to Brâncovenesc. The Periodization of Romanian Art in the Second Half of the Nineteenth Century”. In: Kallestrup, Shona et al. (eds.) Periodization in the Art Historiographies of Central and Eastern Europe. New York, London: Routledge, 48–67.Mishkova, Diana. 2023. Rival Byzantiums. Empire and Identity in Southeastern Europe. Cambridge: Cambridge University Press.Miyatev, Krastyu. 1927. „Monumentalnata zhivopis v drevna Bulgaria“. V: GSU, VI, Bogoslovski fakultet. Sofia: Hudozhnik, 131–146. [in Bulgarian]Miyatev, Krastyu. 1936. Poganovskiyat manastir. Sofia: TsBD. [in Bulgarian]Miyatev, Krastyu. 1965. Arhitekturata v srednovekovna Bulgaria. Sofia: BAN. [in Bulgarian]Mutafov, Chavdar. 1927. „Rodna arhitektura“. Arhitekt, 1: 19–23. [in Bulgarian]Mutsopulos, Nikolaos. 2007. Bazilikata „Sveti Ahiliy“ v Prespa. Edin istoricheski pametnik-svetinya. Plovdiv: Vion. [in Bulgarian]Naksidu, Eleonora. 2019. „Ot Ohrid do Solun: Margaritis Dimitsas i negovoto „makedonsko patuvane“. V: Konstantinova, Yura (sast.) Solun i balgarite: istoria, pamet, savremie. Sofia: BAN, 88–109. [in Bulgarian]Nastasă, Lucian. 1997. “Orest Tafrali și studiile de bizantinologie”. Cercetări istorice, XVI: 157–172.Neshkova, Reni. 2020. „Emanuel Mutafov: Drazni me proletarskoto otnoshenie kam intelektualnia trud“. Glasove, 10.09.2020 g., https://glasove.com/kino/emanuel-mutafov-drazni-me-proletarskoto-otnoshenie-kym-intelektualniya-trud (posledno poseten na 11.10.2024 g.). [in Bulgarian]Orlándos,  Anastásios.  1938.  “Ta byzantiná mnhmía ths Kastoriás”.  ABME,  D':  2-216. [in Greek]Ovcharov, Nikolay. 1994. Prouchvania varhu srednovekovieto i po-novata istoria na Vardarska Makedonia. Novo sled Yordan Ivanov. Sofia: Universitetsko izdatelstvo „Sv. Kliment Ohridski“.[in Bulgarian]Pantelić, Bratislav. 2016. “The Last Byzantines: Perceptions of Identity, Culture, and Heritage in Serbia”. Nationalities Papers, 44 (3): 430–455.Paviћeviћ, Aleksandra. 2005. „Shta radi i gde sedi „Beli anђeo“?“. Glasnik EI SANU, LIII: 185–193.pelekanídhs,  Stylianós.  1960.  Byzantiná kai metabyzantiná mnhmía ths préspas.  Thessaloníkh:  IMCHA. [in Greek]Pelekanidis, Stylianos and Chatzidakis, Manolis. 1985. Kastoria. Athens: Melissa.Penkova, Biserka. 2011. „Kam iztochnitsite na stila na stenopisite ot 1259 g. v Boyanskata tsarkva“. V: Penkova, Biserka (sast.) Boyanskata tsarkva mezhdu Iztoka i Zapada v izkustvoto na hristiyanska Evropa. Sofia: NIM, 248–258. [in Bulgarian]Perdrizet, Paul. 1907. « Melnic et Rossno ». Bulletin de correspondance hellénique, 31 (1): 20–37.Petković, Vladimir. 1930. La peinture serbe du Moyen Âge. Belgrade: Musée d’histoire de l’art.Petkoviћ, Vladimir. 1924. Stari srpski spomenitsi u Јuzhnoј Srbiјi. Beograd-Zemun: Makariјe.Petkoviћ, Vladimir. 1926a. „A. Protich. Yugozapadnata shkola v balgarskata stenopis prez XIII i XIV v.“. Prilozi za kњizhevnost, јezik, istoriјu i folklor, 6 (1): 153–156.Petkoviћ, Vladimir. 1926b. „A. Protitch. Un modèle des maîtres bulgares du XV et XVI siècle”. Prilozi za kњizhevnost, јezik, istoriјu i folklor, 6 (1): 150–153.Petrov, Petar. 1993a. Bogdan Filov. Patuvania iz Trakia, Rodopite i Makedonia 1912-1916. Sofia: Universitetsko izdatelstvo „Sv. Kliment Ohridski“.[in Bulgarian]Petrov, Petar. 1993b. Nauchna ekspeditsia v Makedonia i Pomoravieto 1916. Sofia: Sv. Georgi Pobedonosets. [in Bulgarian]Popoviћ, Pera i dr. 1933. Staro Nagorichino. Psacha. Kaleniћ. Beograd: SKA.Protich, Andrey. 1925. „Yugozapadnata shkola v balgarskata stenopis prez XIII i XIV v.“. V: Sbornik v chest na Vasil N. Zlatarski. Sofia, 291–342. [in Bulgarian]Protich, Andrey. 1930. Denatsionalizirane i vazrazhdane na balgarskoto izkustvo prez turskoto robstvo ot 1393 do 1879 god. Sofia. [in Bulgarian]Pyatnitsky, Yuri. 2011. “An Imperial Eye to the Past: Byzantine Exhibitions in the State Hermitage Museum, 1861–2006”. Tyragetia, V (2): 71–98.Rashenov, Aleksandar. 1932. „Balgarska shkola vav vizantiyski stil“. IBAI, 6: 206–220.Rohdewald, Stefan. 2022. Sacralizing the Nation through Remembrance of Medieval Religious Figures in Serbia, Bulgaria and Macedonia, vols. 1–2. Leiden, Boston: Brill.Ruseva, Ralitsa. 2009. „Belezhki varhu atributsiyata, avtorstvoto i ktitorite na nyakoi ot proizvedeniyata na tsarkovnoto izkustvo ot manastira „Sv. Bogoroditsa Kosinitsa“, sahranyavani v NIM“. INIM, XX: 165–187. [in Bulgarian]Ruseva, Ralitsa. 2011. „Istoria, atributsia i analiz na proizvedenia na tsarkovnoto izkustvo ot taka narechenia „spets-fond“, sahranyavani v Natsionalnia istoricheski muzey, Sofia. (II)“. INIM, HHІІІІ: 253–286. [in Bulgarian]Ruseva, Ralitsa. 2023. „Razvitie i razprostranenie na ikonografiyata na Sv. Naum Ohridski Chudotvorets (XIV–XIX v.)“. V: Hristova-Shomova, Iskra (sast.) Tvardina na pravoslavieto. Proslava na Sveti Naum Ohridski. Sofia: Universitetsko izdatelstvo „Sv. Kliment Ohridski“, 29–67. [in Bulgarian]Stevović, Ivan. 2018. “Medieval Art and Architecture as an Ideological Weapon: the Case of Yugoslavia”. Проблеми на изкуството, 2: 3–8.Stevoviћ, Ivan. 2021. „L’ancien art serbe. Les églises јedan vek kasniјe“. U: Preradoviћ, Dubravka i Markoviћ, Miodrag (ured.) Gabriel Miјe i istrazhivaњa stare srpske arhitekture. Beograd: SANU, 289–312.Strahilov, Ivo i Karakusheva, Slavka. 2015. „Osmanskoto minalo – mezhdu nasledenoto i nasledstvoto“. Seminar_BG, 12, https://www.seminar-bg.eu/spisanie-seminar-bg/broy12/631-osmanskoto_minalo.html  (last seen 11.10.2024) [in Bulgarian]Strezov, Georgi. 1891. „Dva sandzhaka ot Iztochna Makedonia“. Periodichesko spisanie na BKD, XXXVI: 809–860.Swthríoy,  Yeóryios.  1942.  Christianikí kai byzantiní archaioloyía,  A'.  Athínai. [in Greek]Swthríoy,  Yeóryios.  1945.  «H téchnh twn byzantinón mnhmíwn ths Meshmbrías».  Sto:  Mégas,  Yeóryios (epim. ) H Meshmbría toy Evxínoy,  A'.  Athínai:  Estía,  161–173. [in Greek]Swthríoy,  Yeóryios.  1949.  «O byzantinós naós toy Ag.  Achillíoy ths préspas kai ai boylgarikaí perí ths idrísews títoy apópsis».  pAA,  20:  8–14. [in Greek]Todorov, Georgi. 2001. „Razbitoto sartse na grad Sv. Sofia, unishtozhavaneto na sofiyskite svetini pri kmeta Dimitar Petkov (1888–1893)“. Kultura, 1 mart 2001 g., https://newspaper.kultura.bg/bg/article/view/5142  (last seen 11.10.2024 ) [in Bulgarian]Todorov, Petar. 2021. “Production of Territoriality in the Balkans: The Border and the Monastery St. Naum”. In: Stefanov, Nenad and Radović, Srdjan (eds.) Boundaries and Borders in the Post-Yugoslav Space: A European Experience. Berlin, Boston: De Gruyter Oldenbourg, 167–188.Todorova, Maria. 1986. „Machiel Kiel, Art and Society of Bulgaria in the Turkish Period. Van Gorcum, Assen / Maastricht, 1985, 400 p.“. Vekove, 4: 81–85. [in Bulgarian]Trencheva, Keti. 2024. „Kostite na tsar Samuil - mezhdu 'grobomaniyata' i politicheskata upotreba“.  Balgarsko natsionalno radio, 10.10.2024 g., https://bnr.bg/horizont/post/102057447 (last seen 11.10.2024.). [in Bulgarian]Tuleshkov, Nikolay. 2001. Arhitekturnoto izkustvo na starite balgari, t. 1. Sofia: Izdatelstvo na BAN „Prof. Marin Drinov“, Arh & Art. [in Bulgarian]Üre, Pınar. 2014. “Byzantine Heritage, Archaeology, and Politics Between Russia and the Ottoman Empire: Russian Archaeological Institute in Constantinople (1894–1914)”. PhD diss., LSE.Vaklinov, Stancho. 1977. Formirane na starobalgarskata kultura VI–XI vek. Sofia: Nauka i izkustvo. [in Bulgarian]Valkov, Martin. 2018. „Mezhdu natsionalno obedinenie i zavoevatelna voyna: voennopoliticheskite tseli na Bulgaria prez Parvata svetovna voyna kato istoriografski problem“. Anamneza, 1: 1–47, http://anamnesis.info/node/1381 (posledno poseten na 11.10.2024 g.) [in Bulgarian]Vasiliev, Asen. 1965. Balgarski vazrozhdenski maystori. Zhivopistsi, rezbari, stroiteli. Sofia: Nauka i izkustvo. [in Bulgarian]Vezenkov, Aleksandar i Marinov, Chavdar. 2015. „Kontseptsiyata za natsionalno Vazrazhdane v balkanskite istoriografii“. V: Daskalov, Rumen i Vezenkov, Aleksandar (sast.) Prepletenite istorii na Balkanite, t. 3. Sofia: Izdatelstvo na NBU, 420–478. [in Bulgarian]Xyngopoulos, Andreas. 1955. Thessalonique et la peinture macédonienne. Athènes: Myrtidis.Xyngopoulos, Andreas. 1956. Manuel Panselinos. Athens’ Editions.Xyngópoylos,  Andréas.  1931.  “A Protic.  Les oriyines sassanides et byzantines de l’art bulgare”.  Epethrís Etairías Byzantinón Spoydón,  8:  354–354. [in Greek]Yordanova, Lilyana. 2022. “Between Concepts and Realities: The Boyana Church as a "Mirror" of Its Patrons?” In: Boyanov, Ilian (ed.) The Boyana Church Between the East and the West in the Cultural and Historical Context of the 13th Century. Sofia: National Museum of History, 27–57.Zhivkova, Lyudmila. 1980. Chetveroevangelieto na tsar Ivan Aleksandar. Sofia: Nauka i izkustvo. [in Bulgarian]
Keywords: art history; old Bulgarian art; medieval heritage; wars; Macedonia